2016
DOI: 10.1111/psyp.12685
|View full text |Cite
|
Sign up to set email alerts
|

When anger dominates the mind: Increased motor corticospinal excitability in the face of threat

Abstract: Threat demands fast and adaptive reactions that are manifested at the physiological, behavioral, and phenomenological level and are responsive to the direction of threat and its severity for the individual. Here, we investigated the effects of threat directed toward or away from the observer on motor corticospinal excitability and explicit recognition. Sixteen healthy right‐handed volunteers completed a transcranial magnetic stimulation (TMS) task and a separate three‐alternative forced‐choice emotion recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 102 publications
4
33
1
Order By: Relevance
“…A growing body of literature concurs with evolutionary accounts by highlighting a functional and anatomical link between neural systems that sustain emotional appraisal and those that underlie action preparation (de Gelder, Snyder, Greve, Gerard, & Hadjikhani, 2004; Grèzes, Valabregue, Gholipour, & Chevallier, 2014; Pichon, de Gelder, & Grezes, 2012; Van den Stock, 2011). Moreover, and in agreement with the present results, the influence of emotion stimuli on motor-related areas was observed from 150ms to 300ms post-stimulus onset (Borgomaneri, Gazzola, & Avenanti, 2014; Conty et al, 2012; El Zein, Gamond, Conty, & Grèzes, 2015a; El Zein et al, 2015b; Hortensius, de Gelder, & Schutter, 2016). We therefore suggest that the early potentiation of premotor activity during emotion decisions is related to the behavioral relevance for the observer of the perceived threat rather than its sensory properties.…”
Section: Discussionsupporting
confidence: 93%
“…A growing body of literature concurs with evolutionary accounts by highlighting a functional and anatomical link between neural systems that sustain emotional appraisal and those that underlie action preparation (de Gelder, Snyder, Greve, Gerard, & Hadjikhani, 2004; Grèzes, Valabregue, Gholipour, & Chevallier, 2014; Pichon, de Gelder, & Grezes, 2012; Van den Stock, 2011). Moreover, and in agreement with the present results, the influence of emotion stimuli on motor-related areas was observed from 150ms to 300ms post-stimulus onset (Borgomaneri, Gazzola, & Avenanti, 2014; Conty et al, 2012; El Zein, Gamond, Conty, & Grèzes, 2015a; El Zein et al, 2015b; Hortensius, de Gelder, & Schutter, 2016). We therefore suggest that the early potentiation of premotor activity during emotion decisions is related to the behavioral relevance for the observer of the perceived threat rather than its sensory properties.…”
Section: Discussionsupporting
confidence: 93%
“…When looking at later time points, specifically 300 ms, effects seem to be driven by actions in general rather than being emotion specific ( Borgomaneri et al, 2012 ). On the other hand, Hortensius et al (2016) found an effect of anger compared to both fear and neutral at 300 ms. In the current study, we used the time points 200, 400, 500, and 700 ms.…”
Section: Discussionmentioning
confidence: 86%
“…This also means, however, a possibly critical difference between our task and previous studies that did find modulation of MEP amplitude in response to whole body expressions of emotion, namely the explicit identification of the emotional content of the stimulus. Indeed, all previous studies included the recognition of the expressed emotion in the body stimulus, either by verbal report or button press ( Borgomaneri et al, 2012 , 2014 , 2015a , b , 2017 ; Hortensius et al, 2016 ). Whether such task manipulations actually influence the state of the motor cortex has not been directly tested yet, although similar discrepancies between results originating from differences in task instructions can be observed in emotion sensitive regions such as the amygdala ( de Gelder et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also support this view. For instance, Hortensius et al (2016) aimed to explore the threat detection advantage of body stimuli. In their study, fearful/angry body stimuli were directed toward or away from the observer.…”
Section: Discussionmentioning
confidence: 99%